Rehabilitation management of a triceps surae muscle injury in a young male with haemophilia A and high-titre inhibitors - Frizziero, Antonio; Finotti, Paolo; Costantino, Cosimo; Pasca, Samantha; Zanon, Ezio (Acta Biomedica Atenei Parmensis, 2021)
Haemophilia A is a rare inherited hematologic disorder characterized by a deficit of coagulation factor VIII. It is associated with frequent episodes of musculoskeletal bleedings that occur mainly inside joints and secondly inside muscles. The majority of intramuscular hematomas respond well to conservative protocols, based on rehabilitation techniques and appropriate haemostatic coverage; surgery is limited to refractory cases. This manuscript describes the management of an intramuscular bleeding in a young patient with severe haemophilia A and high-titre inhibitors. A multidisciplinary approach directed by a physiatrist and combining surgical intervention, use of bypassing agents and rehabilitation treatment allowed to successfully managing this case, leading to a complete functional recovery. Given the lack of consensus on the treatment of intramuscular bleedings in haemophiliac patients, this case report provides an example of successful management for such conditions, which require a multidisciplinary approach in which the physiatrist plays a key role.